Determinan Harga Saham pada Sektor Perusahaan Perbankan Syariah yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2021-2024 - Hutasoit, Ritjka Benela; Puteri, Hesi Eka (Lembaga Yasin AlSys, 2026)
The influence of financial ratios on the stock prices of Islamic banking companies has received attention in several studies, yet research that specifically analyzes the effect of Return on Equity (ROE), Capital Adequacy Ratio (CAR), and Non-Performing Financing (NPF) on the stock prices of Islamic banking companies listed on the Indonesia Stock Exchange for the 2021–2024 period remains limited. This study aims to analyze the effect of ROE, CAR, and NPF on the stock prices of Islamic banking companies. This study used a quantitative approach with an explanatory research design based on panel data regression. The research sample consisted of four Islamic banking companies selected through purposive sampling. Data were collected through documentation based on quarterly financial statements and company stock price data during the 2021–2024 period, and were then analyzed using panel data regression with the assistance of EViews version 13. The results show that ROE and CAR have a positive and significant effect on stock prices, whereas NPF has a negative and significant effect on the stock prices of Islamic banking companies. Simultaneously, ROE, CAR, and NPF have a significant effect on stock prices, with an Adjusted R-squared value of 77.7055%. This finding contributes to the development of signaling theory and broadens understanding of the influence of financial performance on stock prices in the Islamic banking sector in Indonesia. The conclusion of this study emphasizes the importance of profitability, capital adequacy, and financing quality in increasing investor confidence in the stocks of Islamic banking companies. The implications of this study include theoretical contributions to enriching the literature on the Islamic capital market and practical implications for companies and investors in making investment decisions based on financial performance.